The Evaluation of Lobbying Regulations in the EC and the EP According to the Project of International Standards of Non-Governmental Organisations - Babák, David; Pitrová, Markéte (Czech Journal of International Relations, 2018)
The current lobbying regulation system in the EU (the EP and the EC), in the form of the official documentation, lacks in many ways according to the project of International Standards for Lobbying Regulation. According to this project, the system is the strongest in its regulatory scope and transparency, and the weakest in the areas of oversight, sanctions, and integrity. The outcome of our analysis is in accordance with the EU’s voluntary and self-regulatory system. The analysis has also shown that the European Commission fulfils over 50 % of the established standards. In contrast, the European Parliament fulfils less than 50 %. There is definitely a large space for improvement for both of these EU institutions, especially in the areas of integrity, participation, and access. The main problems of the Union regulation are inconsistency, a voluntary transparency register, the insufficiency of the data provided in the register, the absence of an independent oversight institution and stricter sanctions, and the lenient use of legislative footprints.